2021
DOI: 10.21037/tlcr-21-677
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of pulmonary lymphangitic carcinomatosis in patients with non-small cell lung cancer

Abstract: Background:The eighth edition of the TNM classification for lung cancer does not provide a definite guideline for pulmonary lymphangitic carcinomatosis. The purpose of this retrospective case-control study is to evaluate the prognosis of pulmonary lymphangitic carcinomatosis in patients with non-small cell lung cancer compared with those with intrapulmonary metastases.Methods: Non-small cell lung cancer (NSCLC) patients with pulmonary lymphangitic carcinomatosis detected on chest computed tomography scan durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“… 37 As per previous studies, approximately 5.5% of PLCs are associated with lymphangitis carcinomatosa, a feature not described in PLS. 38 In our study, carcinoma frequently showed a higher mean age, male predilection, smaller size at presentation, higher mean postcontrast attenuation, irregular shape, spiculated margins, and frequent distant metastasis with statistically significant difference. Background emphysematous changes, although not statistically significant, were seen 32.1% of carcinomas and only in one patient with sarcomatoid carcinoma, likely due to the higher association with smoking in carcinomas.…”
Section: Discussionsupporting
confidence: 47%
“… 37 As per previous studies, approximately 5.5% of PLCs are associated with lymphangitis carcinomatosa, a feature not described in PLS. 38 In our study, carcinoma frequently showed a higher mean age, male predilection, smaller size at presentation, higher mean postcontrast attenuation, irregular shape, spiculated margins, and frequent distant metastasis with statistically significant difference. Background emphysematous changes, although not statistically significant, were seen 32.1% of carcinomas and only in one patient with sarcomatoid carcinoma, likely due to the higher association with smoking in carcinomas.…”
Section: Discussionsupporting
confidence: 47%
“…Several malignancies are associated with PLC; primary lung cancer is a common cause of PLC. [1][2][3] The role of 18 F-FDG PET/CT in staging, prediction of prognosis, and assessment of response to therapy in lung cancer is well established, and literature suggests an incremental role of 18 F-FDG PET/CT in detection of the PLC as well. [4][5][6] PLC usually responds poorly to chemotherapy and is associated with poor prognosis.…”
Section: Figurementioning
confidence: 99%
“…PLC is associated with infiltration of the malignant cells through the lymphatics in the pulmonary vasculature from the primary site. Several malignancies are associated with PLC; primary lung cancer is a common cause of PLC 1–3 . The role of 18 F-FDG PET/CT in staging, prediction of prognosis, and assessment of response to therapy in lung cancer is well established, and literature suggests an incremental role of 18 F-FDG PET/CT in detection of the PLC as well 4–6 .…”
mentioning
confidence: 99%